Improving Individual and Team Performance Through the Concept of Servant Leadership in the Work Environment: Literature Review - Suretno Samuel Sianturi; Yunia Wardi; Ilham Thaib (Dinasti Publisher, 2024)
This research aims to theoretically understand the concept of service leadership and explore its impact on individual and team performance in the workplace. The method used in this research is a systematic literature review. The SLR approach applied in this research is as follows: the first stage is to collect literature, then analyze it, and finally conduct a content analysis where the SLR findings are discussed and conclusions are drawn. The findings explain that servant leadership is closely related to leadership ethics, perceived organizational support, self-efficacy, creativity, work engagement, and intrapreneurial ability. Leaders who practice servant leadership tend to create work environments that are inclusive and values-based and encourage individuals' personal and professional growth. Servant leadership can be considered a powerful and relevant approach to building an ethical, innovative, and high-performing organizational culture.